PERBAIKAN PENANGANAN PASCA PANEN KAKAO BAGI PETANI DI DESA ASAHDUREN KECAMATAN PEKUTATAN KABUPATEN JEMBRANA, BALI - Singapurwa, Ni Made Ayu Suardani; Nursini, Ni Wayan; Suariani, Luh; Sudewa, I Ketut Agung; Viani, Agata; Jiwantara, Gusti Ngurah Oka; Winduyasa, I Wayan; Djelantik, Sang Ayu Made Agung Prasetiawati (Universitas Mataram, 2024)
Cocoa is the main commodity produced in Asahduren Village, Pekutatan District, Jembrana Regency, Bali. The PM-UPUD program aims to increase the development of farmer groups and Micro, Small, and Medium Enterprises to increase the empowerment of community members based on cocoa plantations which include cocoa cultivation technology and post-harvest technology for cocoa plants. The farmer groups as PM-UPUD partners are the Mekar Nadi Farmer Group and the Tunas Jaya Farmer Group, both of which are located in Asahduren Village, Pekutatan District, Jembrana, Bali. Partner problems include the quality of the cocoa beans produced and the lack of skills in the cultivation and post-harvest handling of cocoa plants. The activity methods used are surveys, counseling, direct practice, monitoring, and evaluation. The results of the PM-UPUD activities are that the Mekar Nadi Farmer Group and the Tunas Jaya Farmer Group have the ability and skills in cocoa cultivation and post-harvest handling of cocoa plants in an integrated and integrated manner. The skills that have been implemented by the partner group from the PM-UPUD program in 2023 include the application of cocoa cultivation technology and the application of cocoa bean fermentation technology. Farmer groups have been able to produce fermented cocoa beans which have a higher selling value.